MORPHOLOGICAL CHANGES OBSERVED IN THE HEART MUSCLES AS A RESULT OF DISORDERS IN THE REGULATION OF HYPERKALEMIA, HYPOMAGNESEMIA, HYPOKALEMIA, AND HYPONATREMIA EXCHANGE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Mineral metabolism plays a crucial role in maintaining the structural and functional integrity of the cardiac muscle. Imbalance in macro- and microelements such as potassium, calcium, magnesium, and sodium disrupts ionic homeostasis, leading to morphological and structural changes in the heart tissue. This study focuses on examining the morphological and biochemical alterations occurring in the myocardium of rats under conditions of disturbed mineral metabolism, based on biochemical analyses.